2016
DOI: 10.1002/dc.23520
|View full text |Cite
|
Sign up to set email alerts
|

A case report of CIC‐rearranged undifferentiated small round cell sarcoma in the cerebrum

Abstract: CIC-rearranged undifferentiated small round cell sarcoma (CIC-rearranged USRCS) is a recently established type of Ewing-like small round cell sarcomas, characterized by CIC gene rearrangement, most commonly CIC-DUX4 fusion. This report presents the second case of CIC-rearranged USRCS arising primarily in the cerebrum. A 64-year-old otherwise healthy woman presented with a 1 × 1 cm sized hemorrhagic subcortical tumor in the left temporo-parietal lobe. The tumor repeatedly recurred, and the patient underwent thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
(21 reference statements)
1
18
0
Order By: Relevance
“…Cytologic findings of CIC‐DUX4 sarcomas have been described rarely in literature. Ito et al reported a CIC‐DUX4 sarcoma in the cerebrum with cytologic features of round to ovoid nuclei with mild pleomorphism, finely granular chromatin and some with prominent nucleoli (Table ). Some nuclei were eccentrically placed with vacuolated cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Cytologic findings of CIC‐DUX4 sarcomas have been described rarely in literature. Ito et al reported a CIC‐DUX4 sarcoma in the cerebrum with cytologic features of round to ovoid nuclei with mild pleomorphism, finely granular chromatin and some with prominent nucleoli (Table ). Some nuclei were eccentrically placed with vacuolated cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being generally categorised as undifferentiated round‐cell sarcomas , there is a certain degree of cytomorphological heterogeneity within these tumours 11 . There are only a few reports of cytomorphological features of CIC‐DUX4‐ positive sarcomas on fine needle aspirates 12‐14 . We present cytomorphological features of a rare case of a CIC‐DUX4 fusion‐positive sarcoma, confirmed by reverse transcriptase (RT)‐polymerase chain reaction (PCR), in a paediatric patient.…”
Section: Introductionmentioning
confidence: 91%
“…11 There are only a few reports of cytomorphological features of CIC-DUX4-positive sarcomas on fine needle aspirates. [12][13][14] We present cytomorphological features of a rare case of a CIC-DUX4 fusion-positive sarcoma, confirmed by reverse transcriptase (RT)-polymerase chain reaction (PCR), in a paediatric patient.…”
Section: Cic-rearranged Tumours Including Cic-dux4-and Cic-foxo4-mentioning
confidence: 99%
See 2 more Smart Citations